PARADIGMA LAYANAN KEPUASAN PELANGGAN DALAM PROFESIONALITAS BIMBINGAN DAN KONSELING - Rosita Endang Kusmaryani (Paradigma, 2010)
The change and growth of society strive for the adjustment of Guidance and Counseling professionals toward the appropriate demands, expectations and needs of society. The improvement efforts of this profession have been done to pursue public trust. This close relationship with services efforts profession seemingly has its unique characteristics. Given help services constitute an essential professional obligatory for Guidance and Counseling professionals. In giving services, the profession ought to consider its counselee satisfaction as its customer. The customers encompass as internal customers (college students or teachers of Guidance and Counseling) and external customers (schools’ students, students’ parents and wide range of society). This dichotomy because of the customers would determine in enhancing profession toward the better directions. Customers’ satisfactory service concepts constitute a part of profession improvement besides of improvement in counseling profession standardization, ethic and its convinced direction. This concept is expected could complete counselors’ performance in giving services, moreover they will be able to be superiority mark compared with other professions. The concept of customers’ satisfaction needs to be started from educational institution. In implementing this management concept, educational institution needs to notice some points needed by internal and external customers dealt with giving Guidance and Counseling services. Institutions are expected to be able to know and understand customers’ needs. In addition, profession organization roles are important in contribution toward defending and improving professional members’ satisfaction including in it.Keywords : profession, public trust, customer satisfaction